P01.15.A Longitudinal assessment of neurocognition and quality of life in low-grade glioma patients receiving first-line Temozolomide. (5th September 2022) - Darlix, A; Fabbro, M; Monnier, M; Castan, F; Coutant, L; Denis, E; Carriere, M; Menjot de Champfleur, N; Rigau, V; Duffau, H; Guerdoux, E
Abstract: Background: While maximal safe resection is the first therapeutic option in patients with newly-diagnosed diffuse low-grade glioma (DLGG), the timing and choice of further treatments (chemotherapy, radiation therapy or combinations of both) remain controversial. Because the expected survival is long in these young patients, the oncological impact of treatments must be balanced with the possible side effects, in particular regarding neurocognitive functioning and quality of life (QoL). Temozolomide (TMZ), an alkylating agent, is widely used in this setting. Here we aimed at evaluating the feasibility of a longitudinal neurocognitive and QoL assessment in DLGG patients receiving TMZ. Material and Methods: We conducted a prospective study including adult DLGG patients receiving TMZ as first-line treatment after surgical resection(s) or biopsy. Neurocognition and QoL were evaluated longitudinally until progression. The feasibility was evaluated in terms of participation and compliance of a complete neurocognitive and QoL assessment (defined as the completion of these assessments at baseline, 6 months and 12 months). Secondary objectives were the description of the proportion of patients with changes in neurocognitive or QoL scores on TMZ. Results: Of 29 eligible patients, 26 accepted to enter the study (participation rate 86.7%): 57.7% men, median age 45y. Tumor type was distributed as follows: astrocytoma, IDH-mutant 13/26, astrocytoma, IDH wild-type 1/26 and oligodendroglioma, IDH mutant and 1p19q codeleted 12/26. The compliance rate was 95.6% (evaluable in 23 patients as 3 patients had tumor progression within the first 12 months of TMZ). After TMZ, 13.6% of patients experienced a decline of the MoCA score as compared to baseline (from normal to abnormal). Cognitive complaints according to the FACT-COG assessment were stable for 90.9%. The complete cognitive and QoL evaluations (baseline and after 12 months of TMZ) will be presented. Conclusion: Our data shows that a longitudinal evaluation of cognition and QoL is feasible in low-grade glioma patients. It suggests that first-line TMZ does not negatively affect neurocognition and QoL. These results must be evaluated in the long-term setting (evaluations ongoing) and confirmed in a larger, multicenter cohort.